2018
DOI: 10.1002/cbf.3359
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor panobinostat exerts anticancer effects on esophageal squamous cell carcinoma cells by inducing cell cycle arrest

Abstract: Esophageal squamous cell carcinoma (ESCC) is a common malignancy without effective therapy. Histone deacetylase inhibitors (HDACIs) have been demonstrated as an emerging class of anticancer drugs for a range of haematological and solid tumours. However, the effect of HDACIs has not yet been investigated on ESCC cells. In this study, HDACIs were initially considered to have anticancer activity for ESCC, due to the high expression of HDAC genes in ESCC cell lines by analysing expression data of 27 ESCC cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…These proteins tightly control the cell cycle progression, with critical roles in DNA replication and mitosis. On the other hand, they are also important downstream factors in the TP53 pathway [19]. Lv et al reported the network of KIAA0101, TP53, SP1 functioned in breast cancer, and the depletion of KIAA0101 suppressed cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins tightly control the cell cycle progression, with critical roles in DNA replication and mitosis. On the other hand, they are also important downstream factors in the TP53 pathway [19]. Lv et al reported the network of KIAA0101, TP53, SP1 functioned in breast cancer, and the depletion of KIAA0101 suppressed cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the high expression of hist1h1e was more sensitive to tubastatin A, vorinostat, CAY 10603, AR-42, I-BET-762, NPK76-II-72-1, Genentech Cpd 10, navitoclax, PIK-93, PI-103, PHA-793887, WZ3105 and TPCA-1, but resistant to trametinib, selumetinib, rdea119, docetaxel and 17-AAG. Tubastatin A 34 , vorinostat 35 , AR-42 36 and navitoclax (ABT-263) 37 all reported inhibitory effects on the proliferation of esophageal cancer cells. It is speculated that the high expression of HIST1H1E may play a role in drug sensitivity and drug action.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a molecular link of vinblastine exposure and cellular transcriptional activation of TP53 has been reported, but no association to resistance in oncogenic loss of function of wild‐type TP53 has been investigated 35 . Interestingly, panobinostat was reported to block the transcription/translation of mutant TP53 in esophageal squamous cancer 36 and preferentially reduces resistance to EGFR inhibitor treatment in lung cancer independent of EFGR mutation status 37 . As a study in the context of colon cancer previously showed, the therapeutic potential of pharmacological HDAC inhibition (HDACi) is dependent on the TP53 mutation status of cancers and varies from the agent applied, however, no specific tests with panobinostat have been reported 38 .…”
Section: Discussionmentioning
confidence: 99%